The effect of depressive symptoms on quality of life and its different facets in the oldest age population: evidence from the AgeQualiDe prospective cohort study - Liegert, Paula; Pabst, Alexander; Conrad, Ines; van den Bussche, Hendrik; Eisele, Marion; Hajek, André; Heser, Kathrin; Kleineidam, Luca; Weyerer, Siegfried; Werle, Jochen; Pentzek, Michael; Weeg, Dagmar; et al. (Quality of life research, 2024)
The present study aims to investigate the prospective effect of depressive symptoms on overall QoL in the oldest age group, taking into account its different facets.